2016
DOI: 10.1186/s12882-016-0380-x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor treatment ameliorates lupus nephritis through the expansion of regulatory T cells

Abstract: BackgroundGranulocyte colony-stimulating factor (G-CSF) can induce regulatory T cells (Tregs) as well as myeloid-derived suppressor cells (MDSCs). Despite the immune modulatory effects of G-CSF, results of G-CSF treatment in systemic lupus erythematosus are still controversial. We therefore investigated whether G-CSF can ameliorate lupus nephritis and studied the underlying mechanisms.MethodsNZB/W F1 female mice were treated with G-CSF or phosphate-buffered saline for 5 consecutive days every week from 24 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
3
8
0
1
Order By: Relevance
“…The fraction of CD34 + monocytes in blood inversely correlates with the incidence of acute graft‐versus‐host disease in humans . In mice, G‐CSF also mobilizes murine multipotent CD34 + progenitors which favor Treg cell expansion, thereby preventing spontaneous type I diabetes and ameliorating lupus nephritis .…”
Section: Human Macrophage Differentiation Factorsmentioning
confidence: 99%
“…The fraction of CD34 + monocytes in blood inversely correlates with the incidence of acute graft‐versus‐host disease in humans . In mice, G‐CSF also mobilizes murine multipotent CD34 + progenitors which favor Treg cell expansion, thereby preventing spontaneous type I diabetes and ameliorating lupus nephritis .…”
Section: Human Macrophage Differentiation Factorsmentioning
confidence: 99%
“…Recently, new evidence revealed that MDSCs play a crucial role in the regulation of LN. The granulocyte colony stimulating factor treatment ameliorated LN through reducing the number of G-MDSCs and M-MDSCs and promoting the preferential expansion of CD4 + CD25 + Foxp3 + Tregs in the spleen and kidney of NZB/W F1 female mice ( 12 ). Consistent with these results, in our previous study, the proportion of MDSCs in the kidney gradually increased along with the progression of SLE in MRL/lpr lupus-prone mice ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…No differences were seen in the median number of Tregs per μL or in the median frequency of Tregs as percent of CD4 + cells between the groups after mobilization at day 8, either 15 (13)(14)(15)(16)(17)(18)(19) 14 (13)(14)(15)(16) .34 Time to neutrophil engraftment, days 10 (9-11) 10 (9-11) .93 Time to platelet engraftment, days…”
Section: Evaluation Of Tregs During Chemomobilizationmentioning
confidence: 99%
“…Immune suppressive Tregs are found in the microenvironment of malignant tumors, including multiple myeloma, which are associated with poor prognosis [12,13]. New data suggest that enhanced use of G-CSF may induce the generation of Tregs in a dose-dependent manner, which may have a deleterious effect on the immunologic response against tumor cells after ASCT [14,15]. Conversely, other studies report on reduced Treg levels in the leukapheresis products compared with the bone marrow after G-CSF stimulation [16,17].…”
Section: Introductionmentioning
confidence: 99%